Meaning in life, positive cognition, and learning motivation: A mediational analysis among Chinese college students - Shi-hong Liu; Xiao-li Gong; Qi Ji; Qiao-qiao Li; Ming-hui Kong; Xiao-hui Du; Lei-ying Xiang; Zhi-ru Zhu (PLoS ONE, 2025)
Background While a sense of meaning in life is known to boost students' learning motivation, the psychological process explaining how this happens is not well understood. This study investigated whether positive thinking (positive cognition) acts as the crucial bridge connecting these two. Methods We conducted a survey with 345 university students in Chongqing, China. They completed questionnaires measuring their sense of meaning in life (both the search for meaning and the feeling of having it), their tendency for positive thinking, and their motivation for learning (both for internal satisfaction and external rewards). Results We found a clear link: students with a stronger sense of life meaning also reported higher levels of positive thinking and greater learning motivation. More importantly, positive thinking was a key pathway. A students'  sense of life meaning appeared to first nurture a more positive mindset, and this positive mindset, in turn, was what fueled their motivation to learn. This effect was particularly strong for intrinsic motivation (learning for the love of it). For extrinsic motivation (learning for rewards), positive thinking was also a vital link, sometimes serving as the primary channel through which life meaning influenced motivation. Conclusion Positive thinking is a key ingredient that transforms a sense of life meaning into tangible motivation for learning. Our findings suggest that universities could better support students by not only helping them explore life's meaning but also by actively fostering positive cognitive skills. Such programs could improve students' academic engagement and overall well-being.